2020
DOI: 10.1101/2020.07.04.20146027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sample Pooling as an efficient strategy for SARS-COV-2 RT-PCR screening: a multicenter study in Spain

Abstract: Importance: The actual demand on SARS-CoV-2 diagnosis is a current challenge for clinical laboratories. Sample pooling may help to ameliorate workload in clinical laboratories. Objective: to evaluate the efficacy of sample pooling compared to the individual analysis for the diagnosis of CoVID-19, by using different commercial platforms for nucleic acid extraction and amplification. Design and settings: observational, prospective, multicentre study across 9 Spanish clinical microbiology laboratories in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Finally, another SARS-CoV-2 study reported pooled testing results for 2519 samples performed using a pool size of n = 10 or 11. 3 A total of 1243 tests were required to identify every one of the 241 positive individuals in this population with an average infection rate of p = 241 / 2519 = 0.096 (9.6%). 3 In this case Eq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, another SARS-CoV-2 study reported pooled testing results for 2519 samples performed using a pool size of n = 10 or 11. 3 A total of 1243 tests were required to identify every one of the 241 positive individuals in this population with an average infection rate of p = 241 / 2519 = 0.096 (9.6%). 3 In this case Eq.…”
Section: Resultsmentioning
confidence: 99%
“…3 A total of 1243 tests were required to identify every one of the 241 positive individuals in this population with an average infection rate of p = 241 / 2519 = 0.096 (9.6%). 3 In this case Eq. 4 predicts that a somewhat larger number of 2519 × T %(0.096, 10) / 100 = 1853 tests should have been required to identify every infected sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy could potentially increase worldwide testing capacity many times over [6], if used correctly, in the right segment of the population and under the specific historical prevalence of positive results [7,8] and test sensitivity [9]. It has also shown promising results as a screening tool in clinical practice [10,11], and it has been implemented on a large scale to test asymptomatic individuals, showing a considerably increased throughput in testing coverage while maintaining test sensitivity [12]. In addition, the WHO has recently established that group testing for SARS-CoV-2 is a feasible strategy that can increase testing capacity and can be applied in low prevalence settings.…”
Section: Th F T W K F Th T T Gy T B K T 1943 B D Fm ' Gmentioning
confidence: 99%
“…In its simplest form, the pooling test works by constituting a set of individual samples, in the case where the pool is COVID-19 negative, all the individuals are identified as negative and if the pool is positive, further tests would be necessary to identify infected individuals in the group ( Dorfman, 1943 ; Olivier Gossner, 2020 ). This approach has been successfully used in the countries with high technological potential to deal with the lack of screening means ( Mutzel et al, 2020 ; Shani-Narkiss et al, 2020 ), as it has been proposed as a massive screening strategy ( De Salazar et al, 2020 ; Bilder and Tebbs, 2012 ).…”
Section: Introductionmentioning
confidence: 99%